The Movement of STEM Education in Indonesia: Science Teachers’ Perspectives (Jurnal Pendidikan IPA Indonesia, 2019)
Indonesia, as a large country with a wealth of natural resources and abundant human resources, should be a nation that plays a great role in the development of science and technology. STEM education can be used in other scientific fields by utilizing the principles of science, technology, engineering, and mathematics as a basis for learning and developing potential students. This study is aimed at examining the teachers’ perceptions on STEM education in Indonesia including the understanding of STEM definition more deeply. The subjects in this study consist of 117 science teachers from Indonesia. A set of questionnaire which comprises open-ended and closed-ended questions about teachers’ perceptions and understanding regarding STEM education and the 21st century skills preparation were developed and applied. Responses from the science teachers were analysed through interpretive methods in which the participants’ own meanings and points of view were sought. The results indicate that STEM education is quite well understood by the teachers. It is important that we focus on the teachers because they play a critical role in the success of new reforms. The implication is that there is a great need for awareness raising at both government and teacher levels to embrace STEM education.